Penerapan Rekayasa Nilai (Value Engineering) Pada Proyek Konstruksi Pembangunan Rumah Susun BPK RI Kota Gorontalo - Wirandi S. Ali; Mohammad Yusuf Tuloli; Arfan Utiarahman (Transbahasa, 2025)
In construction projects, there are four main aspects that must be considered: cost, time, quality, and occupational safety. One of the biggest challenges is the cost aspect, which often faces issues such as budget overruns, overtime work, and quality degradation. These issues can be categorized as unnecessary costs. One approach that can be used to reduce unnecessary costs is the application of the Value Engineering concept. The implementation of Value Engineering is carried out through field surveys, participatory observations, and secondary data analysis from project documents such as the Budget Plan (RAB), Detailed Engineering Design (DED), and Unit Price Analysis (AHSP). The analysis is conducted through several stages, including the Cost Model, Cost Breakdown, Pareto rule analysis, function analysis, creative stage, Value Engineering analysis, Life Cycle Cost analysis, and recommendation stage. The results show that the application of Value Engineering in architectural works can provide significant cost efficiency. The total savings reached IDR 69,552,162.86, or 10%. Specifically, for wall works, the applied alternative resulted in savings of 7.53% or IDR 62,784,374.25. For door and window frame works, the selected alternative generated savings of 1.09% or IDR 4,503,000.00. Meanwhile, for flooring works, the applied alternative was able to save 1.4% or IDR 2,264,788.61.